Gastroesophageal reflux disease among population of Arar City, Northern Saudi Arabia - Anwar Matar Alsulobi; Nagah Mohamed Abo el-Fetoh; Sara Ghazi Eid Alenezi,; Razan Ahmed Alanazi; Rawan Hamdan Salem Alenazy; Fryail Aied Lafi Alenzy; Amthal Alturqi Alenzi; Aisha Melfy Al Hazmy; Kholoud Obeid Albathaly,; Rehab Jazem Fattal Alruwaili; Ibtisam Matan Alanazi; Ebtihal Ahmad Ali Alghamdi; et al. (Electronic Physician, 2017)
Background: During the recent decade, several studies about prevalence of symptom-based GERD have revealed increase of its prevalence. In addition to the highly disturbing typical symptoms, it has a series of known consequences and may affect the quality of life. Objective: To determine the prevalence of gastroesophageal reflux disease (GERD) as well as their main characteristics and risk factors among the population of Arar City, Northern Saudi Arabia. Methods: A cross-sectional study was carried out on a sample of 302 individuals from population of Arar city from October 01, 2016 to May 30, 2017, using a researcher made questionnaire and checklist. The questionnaire was administrated in online method. Data were analyzed by SPSS version 22, using descriptive statistics and Chi- Square test. Results: total prevalence of GERD among the studied respondents was 61.8%. In 11.8% there was severe pain. Further, 61.8% reported loss of appetite as an associated condition, 57% reported nausea and vomiting, 55.9% indigestion, 55.4% food regurgitation, 41.4% chest pain and 35.5% headache. The main found risk factors were fatty meals in 84.9% followed by coffee drinking in 77.4%, stress in 71%, spicy food in 58.1% NSAD in 24.7% and smoking in 17.2%. There were no significant effect of sex, age, educational level, marital status or occupational status in the occurrence of GERD (p>0.05). Conclusion: This is the first population-based study in Arar, Northern Saudi Arabia, reporting prevalence of GERD. The rate of 61.8% was substantially high. Coffee drinking, stress, spicy food, prolonged use of NSAID, fatty meals and smoking were the reported risk factors. Population-based endoscopic studies are recommended